2021
DOI: 10.4149/neo_2020_200106n17
|View full text |Cite
|
Sign up to set email alerts
|

miR-155-5p increases the sensitivity of liver cancer cells to adriamycin by regulating ATG5-mediated autophagy

Abstract: Liver cancer is the sixth most prevalent cancer worldwide and the third leading cause of cancer-related deaths. Adriamycin (ADR) resistance, which often leads to the progression of malignant tumors, is a major treatment obstacle for liver cancer. It has been confirmed that miR-155-5p could reverse drug resistance in human breast cancer. However, the biological function of miR-155-5p in ADR-resistant liver carcinoma (HepG2/ADR) cells remains unclear. miR-155-5p and ATG5 expression was determined by RT-qPCR and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…while suppression of miR-126 triggered apoptosis and inhibited B-ALL progression in xenograft mice. miR-155 has been identified as an oncogene in many kinds of cancers, including colon, breast, lung, gastric and liver cancer [10][11][12][13][14]. In agreement with its oncogenic roles, miR-155 has been regarded as a therapeutic target in different cancers.…”
Section: Mirnas In Cancersmentioning
confidence: 99%
“…while suppression of miR-126 triggered apoptosis and inhibited B-ALL progression in xenograft mice. miR-155 has been identified as an oncogene in many kinds of cancers, including colon, breast, lung, gastric and liver cancer [10][11][12][13][14]. In agreement with its oncogenic roles, miR-155 has been regarded as a therapeutic target in different cancers.…”
Section: Mirnas In Cancersmentioning
confidence: 99%
“…The impact of miR‐155‐5p on autophagy and apoptosis in HepG2/ADR cells was partly reversed by ATG5 . miR‐155‐5p was shown to overcome ADR resistance in liver cancer by targeting ATG5, which may be used as a target for liver cancer therapy 208 . Antifibrosis activity of quercetin attenuated rabbit tracheal stenosis via the TGF‐β/AKT/mTOR signaling pathway.…”
Section: Atg5: a Potential Drug Targetmentioning
confidence: 99%
“…Speaking of miRNAs, it has been proved that miRNAs are a type of endogenous, small, single-stranded ncRNAs with a length of about 18-24 bases, which regulate the expression of genes at the post-transcriptional level (92,93). Numerous studies have indicated that miRNAs play predominant roles in the process of tumor cell proliferation, invasion, metastasis, relapse, and drug resistance (2,94,95).…”
Section: Link Between Foxm1 and Ncrnas In Breast Cancermentioning
confidence: 99%